2003
DOI: 10.1017/s1047951103001124
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular findings, and clinical course, in patients with Williams syndrome

Abstract: Aims: We investigated the incidence and outcome of cardiac malformations in 53 patients with Williams syndrome. Methods and results:The mean age, and period of follow-up, were 3.6 and 5.3 years, with standard deviations of 4.0 and 5.6 years, respectively. Of the patients, 45 (85%) had cardiovascular anomalies, often combined. Males presented earlier than females, at the ages of 2.1 years, with standard deviation of 2.8 years, as opposed to 4.5 years, with standard deviation of 4.2 years (p < 0.01). Supraval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 28 publications
3
64
1
3
Order By: Relevance
“…[3][4][5][6] Bruno et al reported two cases of mitral valve repair and two cases of mitral valve replacement for severe supravalvular aortic stenosis, 3 and Maisuls et al reported two cases of mitral valve replacement, combined with aortic surgery. 6 However, in these cases severe supravalvular aortic stenosis might have aggravated the mitral competence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6] Bruno et al reported two cases of mitral valve repair and two cases of mitral valve replacement for severe supravalvular aortic stenosis, 3 and Maisuls et al reported two cases of mitral valve replacement, combined with aortic surgery. 6 However, in these cases severe supravalvular aortic stenosis might have aggravated the mitral competence.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although the mechanism of mitral valve prolapse in WS is unclear, histopathological fi ndings of excised mitral tissue have revealed myxomatous degeneration. 3,5,6 This suggests that defi cient elastin may also contribute to the myxomatous change of the mitral valve as a phenotype of connective tissue ab normalities. 7 Therefore, progressive degeneration of the valve and chordae might result in mitral insuffi ciency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cephalometric analysis of soft tissues can be used after 3-5 years of age, after facial soft-tissue structures are developed and stable. Early diagnosis is a key component in the successful management of WS since some of the associated conditions, such as aortic stenosis, require early treatment [3,5]. Also, infant dental care, nutrition counseling and restorative care are extremely important for maximizing the quality of life for patients with WS [14].…”
Section: Discussionmentioning
confidence: 99%
“…The syndrome is caused by a submicroscopic deletion in chromosome 7 implicating the 7q11.23 region (elastin gene) [4]. Early diagnosis of the syndrome is important since many of its features require treatment, and the prognosis can be dramatically improved by early recognition and appropriate management [5]. However, this developmental disorder is well known to be clinically heterogeneous, making diagnosis difficult if based solely on the clinical picture [6].…”
Section: Introductionmentioning
confidence: 99%